IDENTIFICATION OF RADIO RELAY CHANNEL DYNAMICS DATA TRANSFER - Osadchiy , C. I.; Saula , O. A. (Problems of Informatization and Management, 2021)
The transfer function of the radio relay communication channel, the spectral density of natural noise determined as a result of the experiment and the method of identification of this class of systems are given.